Tingkat Kecanduan Bermain Media Sosial Peserta Didik Kelas Xi SMKN 4 Semarang - Lestari, Eka; Juliejantiningsih, Yovitha (Melati Institute, 2024)
Nowadays, social media is one of the common things to use, both at the age of children, adults, and the elderly. The world of education has also given freedom to students to utilize gadgets / smartphones for learning. Not a few social media are also used to find interesting references related to a learning material. However, there are also negative impacts related to this, a lot of students who cannot manage their time properly due to excessive playing social media. The same thing happens to students at SMK N 4 Semarang, especially class XI, they are often seen playing social media during class hours and outside of class hours. This study aims to determine the picture of addiction to playing social media by students. This study uses a quantitative approach with a survey method. This research was conducted at SMK N 4 Semarang with a total population of class XI of 612 students. The samples in this study were class XI Automotive 1, and class XI Mechanical Engineering 1, and XI Automotive 3 with a total of 108 students. Collecting research data using a social media addiction scale. The results obtained from this study are the level of addiction to playing social media in class XI SMK N 4 Semarang mostly in the low category with a percentage of 38%, followed by the medium category with a percentage of 35%, and high with a percentage of 27%.